2008
DOI: 10.1095/biolreprod.107.062943
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of RHOA-Interacting Proteins in Bovine Spermatozoa1

Abstract: In somatic cells, RHOA mediates actin dynamics through a GNA13-mediated signaling cascade involving RHO kinase (ROCK), LIM kinase (LIMK), and cofilin. RHOA can be negatively regulated by protein kinase A (PRKA), and it interacts with members of the A-kinase anchoring (AKAP) family via intermediary proteins. In spermatozoa, actin polymerization precedes the acrosome reaction, which is necessary for normal fertility. The present study was undertaken to determine whether the GNA13-mediated RHOA signaling pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 77 publications
(108 reference statements)
2
53
2
2
Order By: Relevance
“…Additionally, this recombinant RSP3-GST bound to endogenously expressed (mouse testes) ASP, ROPN1, and RIIa (Fig. 7c, We have previously demonstrated that AKAP3 interacts with all four R2D2 proteins in vitro [Fiedler et al, 2007]. In order to determine whether this interac- tion could be demonstrated physiologically, we performed co-immunoprecipitation experiments.…”
Section: Interaction Of R2d2 Proteins With Akapsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, this recombinant RSP3-GST bound to endogenously expressed (mouse testes) ASP, ROPN1, and RIIa (Fig. 7c, We have previously demonstrated that AKAP3 interacts with all four R2D2 proteins in vitro [Fiedler et al, 2007]. In order to determine whether this interac- tion could be demonstrated physiologically, we performed co-immunoprecipitation experiments.…”
Section: Interaction Of R2d2 Proteins With Akapsmentioning
confidence: 93%
“…Mutants that lack RSP11, an ASP/ROPN1 ortholog in the flagellum of Chlamydomonas reinhardtii, display impaired and sporadic motility [Yang and Yang, 2005], suggesting that R2D2 proteins play a role in regulating the physiological functions of flagella. All four R2D2 proteins bind AKAP3 in vitro, and both SP17 and CABYR have been shown to co-precipitate from sperm lysate with AKAP3 [Fiedler et al, 2007;Lea et al, 2004]. However, very little is known about the ability of R2D2 proteins to interact with AKAPs other than AKAP3.…”
Section: Introductionmentioning
confidence: 99%
“…PKA can be targeted to the sperm tail by interaction with tyrosine phosphorylated AKAP3 during capacitation and sperm motility can be improved by enhancing the interaction between AKAP3 and PKA (Luconi et al 2004). The AKAP3 binding to the protein rhophilin-associated protein 1 (ROPN1), containing the RII dimerization/ docking (R2D2) domain, is regulated by PKA phosphorylation (Fiedler et al 2008). The increase in the levels of ROPN1, AKAP4, and AKAP3 in frozen-thawed sperm suggests that these three proteins may play an important role in premature capacitation.…”
Section: Phosphoproteinsmentioning
confidence: 99%
“…Aldolase A is a ubiquitous enzyme, predominantly expressed in muscle, and has been described in the fibrous sheath of mouse and human sperm (Krisfalusi et al 2006, Kim et al 2007). Aldolase B is highly expressed in both kidney and liver whereas aldolase C is found mainly in the nervous system, but has been also identified in bovine spermatozoa (Fiedler et al 2008). In addition, three novel aldolase A isoenzymes are expressed in mouse spermatozoa (Vemuganti et al 2007).…”
Section: Introductionmentioning
confidence: 99%